Synthesis, structural characterization and magnetic properties of the monoclinic ordered double perovskites BaLaMSbO6, with M = Mn, Co and Ni - Blanco, Marìa Cecilia (2014)
Double perovskites BaLaMnSbO6, BaLaCoSbO6 and BaLaNiSbO6, were synthesized by conventional ceramic method in air, as polycrystalline powders. The Mn and Ni compounds belong to the I 2/m monoclinic space group, while the Co perovskite belongs to the I 4/m tetragonal space group. Effective presence of Mn2+ has been well established by X-ray emission spectroscopy for BaLaMnSbO6, and there is no evidence of Mn3+. BaLaCoSbO6 and BaLaNiSbO6 only show the expected 3D-antiferromagnetic behavior typical of super-superexchange interactions, while BaLaMnSbO6 displays signs of superparamagnetism in the 40–160 K range, which arises from unbalanced antiferromagnetism inside nanoclusters formed by regions which are rich in Mn2+–O2−–Mn2+ paths. Neutron powder diffraction data for BaLaMnSbO6 reveals that at 3 K, only long range order antiferromagnetic arrangement of Mn2+ spins on 2d octahedral sites is obtained.